Phaseolus germplasm collection in Mexico - Rodríguez C, M.; Rodríguez T, S.; Aguilar S., M.; Debouck, Daniel G. (1987)
Results are given from a Phaseolus germplasm field study carried out in Southern Nuevo Leon, Mexico: 143 samples of 8 different species. The presence of each one of the species in this part of the country is discussed. (CIAT)